Graphitized carbon loaded high-performance platinum-based catalyst and preparation method thereof

By uniformly loading platinum-based nanoparticles on graphitized carbon support, the problem of insufficient activity and stability of catalysts in fuel cells is solved, and efficient and stable catalyst applications are achieved, especially in the fields of energy conversion and environmental protection.

CN120389055APending Publication Date: 2025-07-29CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH

Patent Information

Application Number
CN202510575856.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-07-29

AI Technical Summary

Technical Problem

In existing proton exchange membrane fuel cells, the corrosion problem of graphitized carbon support leads to insufficient activity and stability of the catalyst, and the increase in the degree of graphitization will reduce the porosity and specific surface area, affecting the uniform dispersion and catalytic activity of platinum particles.

Method used

By uniformly loading platinum-based nanoparticles on the surface of graphitized carbon support, controlling the particle size distribution of platinum-based nanoparticles and the order of graphitized carbon, a high-performance catalyst for uniform dispersion of platinum-based nanoparticles was prepared, and the stability was improved by sol-gel method and pickling treatment.

Benefits of technology

It realizes efficient utilization of catalysts, has good electrochemical activity and corrosion resistance, and can show excellent stability and low cost in various catalytic reactions, breaking through the life bottleneck of fuel cell commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120389055A_ABST
    Figure CN120389055A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fuel cells, and mainly relates to a graphitized carbon-loaded high-performance platinum-based catalyst and a preparation method thereof. Wherein the graphitized carbon loaded high-performance platinum-based catalyst comprises graphitized carbon and platinum-based nanoparticles with uniform size, and the platinum-based nanoparticles are uniformly dispersed and anchored on the surface of the graphitized carbon; the average particle size of the platinum-based nanoparticles is 3-4 nm, and the particle size distribution range is + / -0.5 nm; the order degree R of the graphitized carbon meets the condition that R = ID / IG = 0.9-1.1; iD is a D peak-to-peak value of the Raman spectrum of graphitized carbon, and IG is a G peak-to-peak value of the Raman spectrum of graphitized carbon; the platinum loading capacity of the graphitized carbon loaded high-performance platinum-based catalyst is 20 to 25 percent; and the geometric standard deviation sigma g of the particle size distribution of the platinum-based nanoparticles is less than 1.12. The graphitized carbon-loaded high-performance platinum-based catalyst provided by the invention has good electrochemical activity, platinum-based nanoparticles are uniformly dispersed on a carbon material with a highly graphitized structure in a nanoscale manner, the platinum-based catalyst has good stability and corrosion resistance, and efficient utilization of the catalyst can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fuel cells, and mainly relates to a high-performance platinum-based catalyst supported on graphitized carbon and a preparation method thereof. Background Art

[0002] As a typical representative of clean energy technologies, the cathode catalytic system of proton exchange membrane fuel cells (PEMFCs) needs to meet the dual performance indicators of catalytic activity and durability simultaneously. The design of conventional catalysts often uses high specific surface area carbon carriers, and their developed mesoporous structures endow Pt nanoparticles with excellent dispersion characteristics and high electrochemically active areas. Among them, the carrier-metal interface electronic effect also has a significant regulatory effect on the oxygen adsorption energy, and the structure of the catalyst has a decisive influence on the oxygen reduction activity. The research on heat-treating high specific surface area carbon has been commercialized. Because it is easy to obtain, inexpensive, impurity-free, and does not require the application of complex steps and expensive chemical agents, it shows reasonable corrosion resistance in a three-electrode system.

[0003] However, the carbon corrosion problem of this system under dynamic operating conditions always restricts the battery life. In the transient operating conditions of fuel cells (such as start-stop stages), the abnormal increase in the interfacial potential difference will trigger the corrosion of carbon-based materials. The non-uniform distribution of hydrogen during the start-up process will lead to insufficient hydrogen coverage in local areas of the anode. At this time, the corrosion reaction mainly concentrates on the cathode surface. This transient overpotential will directly accelerate the electrochemical oxidation process of the carbon carrier. This corrosion process will trigger three interrelated failure mechanisms: 1) The collapse of the carrier pore structure directly weakens the mass transfer channel; 2) The non-uniform distribution of ionomers destroys the three-phase reaction interface; 3) The migration and shedding of Pt nanoparticles lead to the loss of active sites. These synergistic effects ultimately cause the mass activity of the catalyst to decay exponentially. By using graphitized carbon as the catalyst carrier, the corrosion resistance and stability can be improved. However, the use of graphitized carbon will also bring some potential problems when improving the material stability: the increase in the degree of graphitization often reduces the porosity and specific surface area of carbon materials, thereby reducing their effective surface area as a carrier. The ordered structure of graphitized carbon may inhibit the uniform dispersion of platinum or platinum-based alloy particles. When platinum particles agglomerate on the carbon surface to form larger particles, their catalytic activity will also be greatly reduced. Therefore, how to improve the stability while achieving efficient and uniform loading on the carbon carrier to maintain its activity and stability in fuel cell reactions is still a major technical challenge. Therefore, the existing technologies still need to be improved and developed. Summary of the Invention

[0004] In view of the above deficiencies of the prior art, the purpose of the present application is to provide a high-performance platinum-based catalyst supported on graphitized carbon and a preparation method thereof, aiming to solve the problem of insufficient activity and stability of existing catalysts.

[0005] The technical solution of this application is as follows: In the first aspect, this application provides a high-performance platinum-based catalyst supported on graphitized carbon, including graphitized carbon and platinum-based nanoparticles with uniform size. Among them, the platinum-based nanoparticles are uniformly dispersed and anchored on the surface of the graphitized carbon; The average particle size of the platinum-based nanoparticles is 3-4 nm, and the particle size distribution range is within ±0.5 nm; The order degree R of the graphitized carbon satisfies R = I D / I G = 0.9-1.1; I D is the peak value of the D peak of the Raman spectrum of the graphitized carbon, and I G is the peak value of the G peak of the Raman spectrum of the graphitized carbon; The platinum loading of the high-performance platinum-based catalyst supported on graphitized carbon is 20-25%; The geometric standard deviation σ of the particle size distribution of the platinum-based nanoparticles g <1.12.

[0006] The high-performance platinum-based catalyst supported on graphitized carbon provided by this application has good electrochemical activity, and the platinum-based nanoparticles are uniformly dispersed on the carbon material with a highly graphitized structure at the nanoscale. It has good stability and corrosion resistance, and can realize the efficient utilization of the catalyst.

[0007] Furthermore, the average particle size of the platinum-based nanoparticles is 3.4-3.9 nm, and the particle size distribution range is within ±0.3 nm.

[0008] In the second aspect, this application provides a preparation method of a high-performance platinum-based catalyst supported on graphitized carbon, which includes the following steps: Mix the graphitized carbon suspension and the platinum-based nanoparticle suspension and then deposit to obtain a precursor; Separate and wash the precursor and then dry it. Heat it in an inert atmosphere and keep it warm. After cooling, perform pickling, and then wash it clean and dry to obtain the high-performance platinum-based catalyst supported on graphitized carbon.

[0009] This application uniformly loads platinum-based nanoparticles on the surface of the graphitized carbon carrier to improve the stability of the catalyst. The graphitized carbon carrier is a carbon material with a highly graphitized structure, and the platinum-based nanoparticles are uniformly dispersed on the graphitized carbon carrier at the nanoscale, thus realizing the efficient utilization of the catalyst and good corrosion resistance. The prepared catalyst has excellent catalytic activity, long-term stability and low cost, and can be applied to a variety of catalytic reactions, especially showing excellent performance in the fields of energy conversion and environmental protection.

[0010] Further, the graphitized carbon suspension is prepared by dispersing graphitized carbon in an organic solvent; The platinum-based nanoparticle suspension is prepared by dispersing platinum-based nanoparticles in an organic solvent; The organic solvent is chloroform.

[0011] Further, the preparation method of the platinum-based nanoparticles comprises the following steps: Adding a platinum precursor and a transition metal precursor into an organic system composed of oleylamine, oleic acid, o-dichlorobenzene and diphenyl ether for reaction, separating the solid and then washing; Every 0.2 g of the platinum-based nanoparticles is dispersed in 30 - 60 mL of the organic solvent.

[0012] Further, the process of the reaction is to heat to 150 - 270 °C at a rated heating rate and keep warm for 10 min - 120 min, and then cool to room temperature; the rated heating rate is 15 - 20 °C / min; The platinum precursor is platinum acetylacetonate, and the transition metal precursor is one or more of nickel acetate, ruthenium acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate; The mass ratio of the platinum acetylacetonate to the transition metal precursor is 1:0.5 - 2.3, and every 0.2 - 0.5 g of the platinum acetylacetonate uses 1.6 mL of oleylamine, 1.6 mL of oleic acid, 9.6 mL of o-dichlorobenzene and 64 mL of diphenyl ether; The washing is carried out by repeatedly centrifuging with a mixed solution of one or both of ethanol and n-hexane, and the centrifugation speed is 10000 rpm.

[0013] Further, the graphitized carbon suspension and the platinum-based nanoparticle suspension are mixed according to the mass ratio of graphitized carbon to platinum acetylacetonate of 0.9 - 1.1:1.

[0014] Further, every 0.35 g of the graphitized carbon is dispersed in 30 - 50 mL of the organic solvent; The preparation method of the graphitized carbon comprises the following steps: Placing the amorphous carbon material in a vacuum high-pressure furnace, performing high-temperature treatment at 1800 - 2600 °C in argon for 75 min, and naturally cooling to room temperature; The amorphous carbon material is KB600.

[0015] Further, the heating temperature is 250 - 550 °C, and the heat preservation time is 10 min - 10 h.

[0016] Further, the conditions for pickling are to soak the precursor in an acidic solution at 50 - 70 °C for 12 hours; Every 0.3 - 0.4 g of the precursor is immersed in 15 ml of the acidic solution; The concentration of the acidic solution is 0.1 - 0.15 mol / L; The acid in the acidic solution is one of perchloric acid, sulfuric acid, nitric acid, and acetic acid; The washing is carried out by repeatedly washing with n - hexane; The condition for washing until clean is to repeatedly wash with ultrapure water until the washing liquid tends to be neutral; The inert atmosphere is argon.

[0017] Beneficial effects: In this application, platinum - based nano - alloy particles are uniformly loaded on the surface of the graphitized carbon support, providing stable support for it and enhancing the stability of the catalyst, preventing the catalyst from agglomerating or losing during the reaction process, thereby improving the long - term stability and durability of the catalyst. The provided catalyst has excellent catalytic activity, long - term stability, and low cost, and can be applied to a variety of catalytic reactions, especially showing excellent performance in the fields of energy conversion and environmental protection. The provided preparation method has high repeatability, can ensure the stable quality of the prepared catalyst, and meet the requirements of large - scale production. Description of the Drawings

[0018] Figure 1 It is a comparison chart of the performance test results before and after graphitization of KB600 in this application.

[0019] Figure 2 It is a TEM image of the graphitized carbon in the example of this application.

[0020] Figure 3 It is an XRD characterization chart of the catalysts in Example 1 and Comparative Example 1 of this application.

[0021] Figure 4 It is a TEM image of the platinum - nickel catalyst in Example 1 of this application.

[0022] Figure 5 It is a TEM image of the platinum - nickel catalyst in Example 1 of this application.

[0023] Figure 6 It is a histogram of the particle size distribution of the platinum - nickel nanoparticles supported by the platinum - nickel catalyst in Example 1 of this application.

[0024] Figure 7 It is a TEM image of the platinum - nickel catalyst supported by commercial carbon in Comparative Example 1 of this application.

[0025] Figure 8 It is a TEM image of the platinum - nickel catalyst supported by commercial carbon in Comparative Example 1 of this application.

[0026] Figure 9This is a histogram of the particle size distribution of the platinum-nickel nanoparticles supported on the commercial carbon-supported platinum-nickel catalyst of Comparative Example 1 of this application.

[0027] Figure 10 This is a TEM image of the platinum-nickel catalyst of Example 2 of this application.

[0028] Figure 11 This is a TEM image of the platinum-nickel catalyst of Example 2 of this application.

[0029] Figure 12 This is a TEM image of the platinum-nickel catalyst of Example 2 of this application.

[0030] Figure 13 This is a TEM image of the platinum-nickel catalyst of Example 2 of this application.

[0031] Figure 14 This is the polarization curve of the platinum-nickel catalyst of Example 2 of this application.

[0032] Figure 15 This is the background current curve of the platinum-nickel catalyst of Example 2 of this application.

[0033] Figure 16 This is the background current curve of the platinum-nickel catalyst of Example 1 of this application measured under 5 cycles of 10,000 times.

[0034] Figure 17 This is the polarization curve of the platinum-nickel catalyst of Example 1 of this application measured under 5 cycles of 10,000 times.

[0035] Figure 18 This is the change in stability ECSA of the platinum-nickel catalyst of Example 1 of this application measured under 5 cycles of 10,000 times.

[0036] Figure 19 This is the change in stability MA of the platinum-nickel catalyst of Example 1 of this application measured under 5 cycles of 10,000 times.

[0037] Figure 20 This is the background current curve of the commercial carbon-supported platinum-nickel catalyst of Comparative Example 1 of this application measured under 5 cycles of 10,000 times.

[0038] Figure 21 This is the polarization curve of the commercial carbon-supported platinum-nickel catalyst of Comparative Example 1 of this application measured under 5 cycles of 10,000 times.

[0039] Figure 22 This is a comparison of the test results of the platinum-nickel catalysts of Example 1 and Comparative Example 1 of this application and the platinum-carbon catalyst of Comparative Example 2.

[0040] Figure 23 This is the MEA test result of the platinum-nickel catalyst of Example 1 of this application.

[0041] Figure 24 This is the MEA test result of the platinum-nickel catalyst of Comparative Example 1 of this application. Detailed implementation manners

[0043] This application provides a high-performance platinum-based catalyst supported on graphitized carbon and a preparation method thereof. To make the purpose, technical solution and effects of this application clearer and more definite, the following further details this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit this application.

[0044] This application provides a high-performance platinum-based catalyst supported on graphitized carbon, including graphitized carbon and platinum-based nanoparticles with uniform size. Among them, the platinum-based nanoparticles are uniformly dispersed and anchored on the surface of the graphitized carbon; The average particle size of the platinum-based nanoparticles is 3-4 nm, and the particle size distribution range is within ±0.5 nm; The platinum loading of the high-performance platinum-based catalyst supported on graphitized carbon is 20-25%.

[0045] Among them, the platinum-based nanoparticles can specifically be nanoparticles of platinum or platinum-based alloys, and are preferably nanoparticles of platinum-based alloys, which can control the cost while maintaining the required activity, and are beneficial to large-scale preparation and application. Moreover, alloying can regulate the d-band center and improve the structural stability of the graphitized carbon support. By controlling the uniform size within a small particle size distribution range, a uniform alloy structure is formed. Relevant lattice contraction can be observed by XRD, which combines with the graphitized carbon support and is uniformly anchored on the surface of the graphitized carbon, having high activity and high stability. At the same time, alloying can inhibit Pt dissolution and has good corrosion resistance.

[0046] The high-performance platinum-based catalyst supported on graphitized carbon provided by this application can have good electrochemical activity at a suitable loading, and the platinum-based nanoparticles are uniformly dispersed on the carbon material with a highly graphitized structure at the nanoscale, and it has good stability and corrosion resistance, and can realize the efficient utilization of the catalyst.

[0047] Furthermore, the average particle size of the platinum-based nanoparticles is 3.4-3.9 nm, and the particle size distribution range is within ±0.3 nm. By further controlling the particle size of the platinum-based nanoparticles, it is convenient for the exertion of its activity and is not easy to agglomerate, and can be uniformly distributed and anchored on the graphitized carbon.

[0048] Furthermore, the geometric standard deviation σ of the particle size distribution of the platinum-based nanoparticles g< 1.12. Specifically, the geometric standard deviation of nanoparticles is an important parameter describing the particle size distribution of nanoparticles, which reflects the width or dispersion degree of the particle size distribution of nanoparticles. The smaller the geometric standard deviation, the more concentrated the particle size of nanoparticles, the narrower the distribution, that is, the particle sizes of most particles are close to the average particle size; conversely, the larger the geometric standard deviation, the wider the particle size distribution of nanoparticles, the greater the difference in particle sizes, and there are more particles with particle sizes deviating from the average particle size. Moreover, the geometric standard deviation of nanoparticles can be used to judge its dispersion degree to a certain extent. Generally speaking, a small geometric standard deviation means better dispersion in terms of particle size, that is, the particle sizes are relatively uniform and the distribution in the system is relatively more uniform; while a large geometric standard deviation indicates relatively poor dispersion of particles, the particle sizes are uneven, and there may be agglomeration or uneven distribution in the system. When the geometric standard deviation σ g of nanoparticles approaches 1, the particle size distribution is very narrow, and the nanoparticles have a high degree of monodispersity, that is, the particle sizes of almost all particles are the same, which is a relatively ideal dispersion state. However, in actual situations, it is very difficult to achieve completely ideal monodispersity. Generally, it is considered that when the geometric standard deviation σ g is between 1.0 - 1.2, the dispersion of nanoparticles is good and belongs to a narrow distribution. When the geometric standard deviation σ g is between 1.2 - 1.5, the dispersion of nanoparticles is medium. At this time, the particle size distribution is relatively wide, there are certain differences in particle sizes, but it is still within an acceptable range, and certain requirements may still be met in some applications. When the geometric standard deviation σ g is greater than 1.5, the dispersion of nanoparticles is poor, the particle size distribution is very wide, the difference in particle sizes is significant, and there may be serious agglomeration phenomena or uneven distribution, which may have an adverse impact on the performance and application of nanoparticles. In this application, the collective standard deviation of platinum-based nanoparticles is controlled to be < 1.2, the particle sizes are uniform, and the dispersion is good, which is beneficial to improving the catalytic performance of the catalyst.

[0049] Among them, for the geometric standard deviation σ g of the particle size distribution of platinum-based nanoparticles, high-resolution images can be directly taken through a transmission electron microscope (TEM), the particle size data of platinum-based nanoparticles can be statistically analyzed by imageJ software, and then the particle size distribution histogram of platinum-based nanoparticles can be drawn according to the data by origin software and its distribution curve can be fitted. Then, by obtaining the median diameter ( d i ) and the corresponding frequency ( w i ) of each particle size interval from the particle size distribution histogram, where if the particle size data is in the form of a frequency distribution, the frequency needs to be converted to a frequency or directly used as a weight. Take the natural logarithm of the median diameter ( d i ) of each interval to obtain ln(d i ), calculate the weighted average of the logarithmic transformation ( μ ln ): , and then calculate the weighted variance of the logarithmic values (σ 2 ln ): , and then take the square root of the variance to obtain the logarithmic standard deviation (σ ln ): , and then exponentiate the logarithmic standard deviation to obtain and calculate the geometric standard deviation (σ g ): .

[0050] Generally speaking, the characteristic of graphitized carbon is that the carbon structure tends to be arranged in a layered graphite structure after heat treatment. As the value of the order degree R continues to decrease, the orderliness increases, and the defects and surface active sites decrease. For example, when the value of the order degree R of graphitized carbon is less than 0.2, the orderliness is high. Clear lattice fringes and continuous atomic planes can be observed in TEM, the interlayer spacing is less than 0.344 nm, the diffraction peak of the <002> crystal plane in XRD is sharp and located at about 2θ = 25.7 degrees, and it has high electrical conductivity and chemical stability. However, its high orderliness also leads to fewer defects and fewer surface active sites, which is likely to limit the loading performance and thus affect the catalytic activity.

[0051] Furthermore, in this application, the order degree R of graphitized carbon satisfies R = I D / I G = 0.9 - 1.1; I D is the peak value of the D peak in the Raman spectrum of graphitized carbon, and I G is the peak value of the G peak in the Raman spectrum of graphitized carbon.

[0052] Specifically, in Raman spectrum characterization, the graphitization degree of the material can be quantitatively analyzed through the characteristic parameters of the D peak (near about 1350 cm -1 ) and the G peak (near about 1580 cm -1 ). Among them, the G peak corresponds to the ordered graphite structure of the in-plane vibration of sp² hybridized carbon atoms, and its full width at half maximum (FWHM) and peak intensity reflect the lattice integrity and orderliness; the D peak is induced by defects or disordered structures (such as sp³ hybridization, grain boundaries or edge defects), and its intensity is positively correlated with the defect density. By calculating the intensity ratio of the D peak to the G peak (I D / I G ) and the FWHM of the G peak, a quantitative evaluation index of the graphitization degree can be established - a lower I D / I G value and a narrower FWHM of the G peak indicate that the material has higher graphitization orderliness, while a higher ID / I G The value and the broadened G peak characterize the enhanced disorder. In this application, the R value is defined as the intensity ratio I D / I G , which is used to measure the degree of order of the structure. The smaller the R value, the fewer the surface defects and the higher the degree of order, which can be used as a criterion for the degree of surface functionalization or graphitization.

[0053] Among them, by controlling the degree of order R within a suitable range in this application, it is beneficial to the loading of the platinum-based catalyst. Specifically, when the degree of order R of the carbon material is greater than 1.1, it is easy to characterize a low-order or amorphous structure, the defects increase, which easily affects the conductivity, mechanical stability and the life of the electrochemical device. When the degree of order R is too low (less than 0.2), the material tends to a perfect graphite structure, which may lead to insufficient surface active sites. By controlling the graphitization conditions described above in this application, the degree of order R of the prepared graphitized carbon can be controlled within 0.9 - 1.1. As a medium-order material, it can achieve a good balance between active sites and stability. Within this degree of order range, it also indicates that the density of defects (such as sp 3 hybridized carbon, grain boundaries or vacancies) in the material remains at a relatively high density, and the size of the sp 2 ordered microcrystals is small. The surface material is close to ordered graphitized carbon. Combining TEM observation, corresponding graphitized lattice fringes can be found, and combining XRD, the sharpness of the diffraction peak of the <002> crystal plane of graphite can also be observed to become higher, indicating that through the setting of this application, a good degree of graphitization can be achieved, and the remaining partial defects are also beneficial to the loading of the platinum-based catalyst.

[0054] Through the setting of this application, the high-performance platinum-based catalyst supported by graphitized carbon has excellent catalytic activity, long-term stability and corrosion resistance, and can control the activity decay after 50,000 cycles of stability test to be <10%. The comprehensive performance of this high-performance platinum-based catalyst is good, and it can be applied to a variety of catalytic reactions, providing an innovative solution for breaking through the life bottleneck of the commercial application of fuel cells.

[0055] This application provides a preparation method of a high-performance platinum-based catalyst supported by graphitized carbon, which includes the following steps: S1. Mix the graphitized carbon suspension and the platinum-based nanoparticle suspension and then deposit them to obtain a precursor; S2. Separate and wash the precursor and then dry it. Heat it in an inert atmosphere and keep it warm. After cooling, perform pickling, and then wash and dry it to obtain a high-performance platinum-based catalyst supported by graphitized carbon.

[0056] In this application, platinum-based nanoparticles are uniformly loaded on the surface of a graphitized carbon support to improve the stability of the catalyst. The graphitized carbon support is a carbon material with a highly graphitized structure, and the platinum-based nanoparticles are uniformly dispersed on the graphitized carbon support at the nanoscale, thereby achieving the efficient utilization of the catalyst and good corrosion resistance, providing a feasible strategy for the preparation and good application of the catalyst. The prepared catalyst has excellent catalytic activity, long-term stability, and low cost, and can be applied to a variety of catalytic reactions, especially showing excellent performance in the fields of energy conversion and environmental protection, providing an innovative solution for breaking through the lifespan bottleneck of the commercial application of fuel cells.

[0057] Further, in step S1, the graphitized carbon suspension is prepared by dispersing graphitized carbon in an organic solvent.

[0058] Further, 0.35 g of graphitized carbon is dispersed in 30 - 50 mL of an organic solvent; the preparation method of the graphitized carbon includes the following steps: placing the amorphous carbon material in a vacuum high-pressure furnace, performing high-temperature treatment at 1800 - 2600 °C in argon for 75 min, and naturally cooling to room temperature to obtain graphitized carbon.

[0059] Among them, the amorphous carbon material can be the commercial amorphous carbon material Ketjenblack (KB600).

[0060] In this application, the stability is improved by using graphitized carbon as the catalyst support. At the same time, by controlling the treatment conditions, the degree of order of the prepared graphitized carbon is controlled within a suitable range, optimizing its pore structure and specific surface area, which can ensure the uniform dispersion of the platinum-based nanoparticles.

[0061] Further, in step S1, the platinum-based nanoparticle suspension is prepared by dispersing platinum-based nanoparticles in an organic solvent.

[0062] Specifically, the specific surface area of the carbon material decreases after graphitization, which easily leads to difficulty in loading the catalyst. In this application, the platinum-based nanoparticles are deposited and prepared by the sol-gel method, and a high loading fraction is achieved through corresponding deposition. Further, the preparation method of the platinum-based nanoparticles includes the following steps: S0: Add a platinum precursor and a transition metal precursor to an organic system composed of oleylamine, oleic acid, o-dichlorobenzene, and diphenyl ether for reaction. After separating the solid, wash to obtain platinum-based nanoparticles.

[0063] Further, in step S0, the reaction process is to heat to 150 - 270 °C at a rated heating rate, hold for 10 min - 120 min, and then cool to room temperature; the rated heating rate is 15 - 20 °C / min.

[0064] Furthermore, the platinum precursor is platinum acetylacetonate (Pt(acac)2); the transition metal precursor is one or more of nickel acetate (Ni(CH3COO)2), ruthenium acetylacetonate, cobalt acetylacetonate, and nickel acetylacetonate; the mass ratio of platinum acetylacetonate to the transition metal precursor is 1:0.5 - 2.3, and for every 0.2 - 0.5 g of platinum acetylacetonate, 1.6 mL of oleylamine, 1.6 mL of oleic acid, 9.6 mL of ortho-dichlorobenzene, and 64 mL of diphenyl ether are used.

[0065] In this application, by alloying platinum (Pt) and transition metal elements in a specific ratio and optimizing the alloying process, the prepared platinum-based nanoparticles have excellent catalytic activity, long-term stability, and low cost. By precisely controlling the synthesis conditions of the platinum-based nanoparticles, they can be evenly dispersed on the surface of the highly graphitized carbon support, effectively reducing the possible aggregation or loss problems of the platinum-based particles during the catalytic process.

[0066] Specifically, oleylamine and oleic acid are used as surfactants. Oleylamine and oleic acid can help the metal atoms of platinum and transition metals to be evenly distributed in the alloy, improving the dispersibility of the alloy. During the synthesis process, they can stabilize the surface of the platinum-based alloy by forming self-assembled structures or through coordination, preventing particle agglomeration during the synthesis. Moreover, through the interaction of their amino or carboxyl groups with the metal surface, they affect the size and morphology of the alloy particles. The amino part of oleylamine can form coordination with the metal surface, and the carboxyl part of oleic acid also has coordination ability, which can limit the growth of metal particles, prevent particle agglomeration, and thus obtain relatively uniform and moderately sized platinum-based nanoparticles.

[0067] Furthermore, after separating the prepared platinum-based nanoparticles, the cleaning can be carried out by repeatedly centrifuging with a mixed solution of one or both of ethanol or n-hexane at a centrifugation speed of 10,000 rpm, and then redispersing in an organic solvent for subsequent deposition.

[0068] Furthermore, in step S1, the organic solvent for preparing the platinum-based nanoparticle suspension and the graphitized carbon suspension is chloroform. Among them, the ratio of the organic solvent to the platinum-based nanoparticles is not fixed. Generally, it is sufficient to ensure the dispersion of the platinum-based nanoparticles in the organic solvent. Specifically, every 0.2 g of platinum-based nanoparticles can be dispersed in 30 - 60 mL of the organic solvent, and adjusted appropriately according to the dispersion state.

[0069] Specifically, chloroform has a relatively low surface tension, which enables it to help metal nanoparticles disperse better and uniformly cover the surface of graphitized carbon. Moreover, as a non-polar solvent, chloroform can dissolve many organic molecules, especially surfactants or organic molecules such as oleylamine and oleic acid. It can effectively dissolve these surfactants and nanoparticles, and through the volatility of chloroform, the dispersed substances of the platinum-based alloy can be evenly distributed on the surface of graphitized carbon. Furthermore, the surface of graphitized carbon usually has some lipophilic functional groups, and the solubility of chloroform can also enable it to penetrate the surface of graphitized carbon, promoting the uniform loading of platinum-based nanoparticles on the surface of graphitized carbon. Through the dispersion effect and volatile characteristics of the chloroform solvent, uniform platinum-based nanoparticles can be left after removing chloroform, and then a uniform loading structure can be formed on the surface of graphitized carbon to ensure the stable existence of the particles on the surface of graphitized carbon. This application improves the interfacial compatibility between graphitized carbon and platinum-based alloy nanoparticles and enhances the synergistic effect between the two.

[0070] Through the preparation method provided by this application, platinum-based nanoparticles with a high degree of uniformity can be prepared. This synthesis method, combined with the characteristics of chloroform dispersion, has a narrow particle size distribution and can load platinum-based nanoparticles with good dispersion, high uniformity, and uniform size on graphitized carbon, which is beneficial to improving the activity of the catalyst.

[0071] Furthermore, in step S1, the graphitized carbon suspension and the platinum-based nanoparticle suspension are mixed in a ratio of 0.9 - 1.1:1 by the mass of graphitized carbon and platinum acetylacetonate. Through the dosage ratio of this application, the overall platinum loading of the platinum-based catalyst supported on graphitized carbon can be controlled to be 20 - 25%, and the loading of transition metals is 3 - 5%. It is not easy to agglomerate and has a low cost, and can maintain good catalytic activity even at a low catalyst loading, meeting the application requirements of activity and stability.

[0072] In this application, after the graphitized carbon suspension and the platinum-based nanoparticles are mixed evenly, they are loaded onto carbon through the dispersion of chloroform, and then static sedimentation is carried out to complete the deposition. Further, in step S2, the washing can be carried out repeatedly with n-hexane.

[0073] Furthermore, in step S2, the inert atmosphere is argon (Ar).

[0074] Furthermore, in step S2, the heating temperature is 250 - 550 °C, and the heat preservation time is 10 min - 10 h. Among them, the heating can be carried out through a tube furnace.

[0075] Furthermore, in step S2, the conditions for pickling are to soak the precursor in an acidic solution (HClO4) at a temperature of 50 - 70 °C for 12 hours.

[0076] Among them, every 0.3 - 0.4 g of the precursor is immersed in 15 ml of an acidic solution; the concentration of the acidic solution is 0.1 - 0.15 mol / L; the acid in the acidic solution is one of perchloric acid, sulfuric acid, nitric acid, and acetic acid.

[0077] In this application, heating treatment can effectively remove residual organic substances and surfactants first, and then acid treatment can improve the stability of the catalyst. Specifically, in the platinum-based catalyst, there may be some residues or oxides during the synthesis process. For example, when preparing a platinum-nickel catalyst, oxides of platinum or nickel (such as PtO2, NiO) may remain. Through pickling, these unnecessary impurities can be effectively removed, making the surface of the platinum-based nanocatalyst cleaner and enhancing the activity and stability of the catalyst.

[0078] Further, in step S2, the washing condition is to wash repeatedly with ultrapure water until the washing liquid tends to be neutral.

[0079] In this application, the high-performance platinum-based catalyst supported on graphitized carbon as described above can be prepared by this preparation method. In this application, a platinum-based nanoparticle is synthesized by the sol-gel method and the nanoparticles are deposited on the graphitized carbon support through subsequent treatment. The operation is convenient, the repeatability is good, the cost is controllable, and it has broad commercial prospects. A platinum-based catalyst with electrochemical activity far greater than that of commercial catalysts can be obtained through this preparation method. Moreover, the prepared catalyst can be applied to a variety of catalytic reactions, especially showing excellent performance in the fields of energy conversion and environmental protection.

[0080] The following is further illustrated by specific examples.

[0081] The preparation method of the graphitized carbon used in the examples of this application includes the following steps: Place KB600 in a vacuum high-pressure furnace, and perform high-temperature treatment at 1800 °C in argon for 75 min, and then naturally cool to room temperature to obtain graphitized carbon.

[0082] XRD (X-ray diffraction), Raman spectroscopy, electron microscopy (TEM), and nitrogen isothermal adsorption / desorption measurements are respectively carried out on KB600 (KB) and the graphitized carbon (GC) obtained after graphitizing KB600 to compare and analyze the structural characteristics and graphitization degree of the carbonaceous materials. The test results are as Figure 1 shown. The TEM of graphitized carbon (GC) is as Figure 2 shown.

[0083] Among them, the XRD patterns of KB600 (KB) and graphitized carbon (GC) are as Figure 1As shown in (a), it can be found that the XRD pattern of KB600 shows a broad peak at around 24.8°, indicating an amorphous structure, while the XRD spectrum of graphitized carbon shows a sharper peak at approximately 25.7°, corresponding to the <002> plane of graphite. This peak is characteristic of the graphite structure, indicating a significant level of graphitization in the graphitized carbon obtained through treatment. The Raman spectra of KB600 (KB) and graphitized carbon (GC) are as shown in Figure 1 (b). The Raman spectrum of KB600 reveals the typical characteristics of amorphous carbon, which are characterized by prominent and overlapping D and G peaks and a weak 2D peak, indicating that the untreated carbon is amorphous and its order parameter R satisfies R KB = I D / I G = 1.279, while the Raman spectrum of graphitized carbon shows that the D peak and G peak of the sample appear at 1332 cm −1 and 1583 cm −1 respectively, which further confirms the structural change of the sample, and the order parameter R of the graphitized sample satisfies R GC = I D / I G = 1.014, indicating that the graphitized carbon after treatment consists of highly graphitized carbon. It can be seen that after the graphitization step of this application, the R value decreases, indicating that the disordered carbon structure is continuously dissolved and the degree of graphitization increases. In addition, in the spectrum of graphitized carbon, the peak at 2661 cm −1 represents a highly ordered graphite lattice, further confirming the increase in the degree of graphitization. These findings are consistent with the XRD results discussed above.

[0084] Figure 1 (c) is the TEM image of KB600 (KB), showing the carbon morphology of KB600, which is usually amorphous with a large number of pores. Figure 1 (f) is the TEM image of graphitized carbon (GC), showing the network structure of graphitized carbon, whose crystal surface spacing is about 0.303 nm, corresponding to the <002> crystal plane of graphite carbon, further confirming that the material has reached a certain degree of graphitization.

[0085] The nitrogen isothermal adsorption / desorption measurement results of KB600 (KB) and graphitized carbon (GC) are as shown in Figure 1 (d), and the corresponding pore structure characterization is as shown in Figure 1 (e). It can be found that the graphitization process causes the specific surface area of KB to decrease from 1519.90 m 2 ·g −1 to 384.04 m 2 ·g −1Due to the dissolution of the disordered structure, the irregular surface and defects of the carbon support during high-temperature treatment are eliminated, and the specific surface area of the carbon support gradually decreases with the increase of the graphitization temperature. Compared with KB, the pore content of GC decreases, and the pore size distribution becomes larger. This may be due to the dissolution and reprecipitation of carbon atoms, resulting in an increase in the pore size of KB and the collapse of super-large pores, causing the disappearance of the original micropores and mesopores in KB after heat treatment, which is basically consistent with the results of the adsorption-desorption curve. It can be seen that the treated carbon support exhibits obvious graphitization characteristics. With the progress of graphitization, the specific surface area and pore volume gradually decrease, and the surface defects further disappear.

[0086] Example 1 The preparation method of the platinum-nickel catalyst of Example 1 includes the following steps: Put 0.416 g of platinum acetylacetonate and 0.54 g of nickel acetate into a three-necked flask of an organic system composed of 1.6 mL of oleylamine, 1.6 mL of oleic acid, 9.6 mL of ortho-dichlorobenzene and 64 mL of diphenyl ether; heat to 200 °C at a heating rate of 15 °C / min, keep warm for 30 min and then cool to room temperature, separate the prepared platinum-nickel nanoparticles, and use a mixed solution of ethanol and n-hexane to repeatedly centrifuge and wash at a centrifugal speed of 10,000 rpm. Then, disperse 0.2 g of platinum-nickel nanoparticles in 45 mL of chloroform to obtain a platinum-nickel nanoparticle suspension.

[0087] Disperse 0.416 g of graphitized carbon in 50 mL of chloroform to obtain the graphitized carbon suspension of Example 1. Mix the graphitized carbon suspension and the platinum-nickel nanoparticle suspension and then deposit to obtain a precursor; Separate and wash the precursor with n-hexane, place it in a tubular furnace, heat to 400 °C in an argon atmosphere and keep warm for 1 hour, cool it, and then soak it in a perchloric acid solution at 60 °C (concentration: 0.1 mol / L) for 12 hours for pickling treatment, and then wash it thoroughly with ultrapure water until the pH value of the washing solution tends to be neutral. After drying, the platinum-nickel catalyst of Example 1 is obtained.

[0088] Example 2 The preparation method of the platinum-nickel catalyst of Example 2 includes the following steps: Put 0.416 g of platinum acetylacetonate and 0.54 g of nickel acetate into a three-necked flask of an organic system composed of 1.6 mL of oleylamine, 1.6 mL of oleic acid, 9.6 mL of ortho-dichlorobenzene and 64 mL of diphenyl ether; heat to 200 °C at a heating rate of 15 °C / min, keep warm for 30 min and then cool to room temperature, separate the prepared platinum-nickel nanoparticles, and use a mixed solution of ethanol and n-hexane to repeatedly centrifuge and wash at a centrifugal speed of 10,000 rpm. Then, disperse 0.2 g of platinum-nickel nanoparticles in 45 mL of chloroform to obtain a platinum-nickel nanoparticle suspension.

[0089] 0.32 g of graphitized carbon was dispersed in 40 mL of chloroform to obtain the graphitized carbon suspension of Example 2. The graphitized carbon suspension and the platinum-nickel nanoparticle suspension were mixed and then deposited to obtain a precursor. The precursor was separated and washed with n-hexane, placed in a tubular furnace, heated to 400 °C in an argon atmosphere and held for 1 hour, cooled, and then immersed in a perchloric acid solution at 60 °C (concentration: 0.1 mol / L) for 12 hours for pickling treatment. Then it was thoroughly washed with ultrapure water until the pH value of the washing solution tended to be neutral, and dried to obtain the platinum-nickel catalyst of Example 2.

[0090] Comparative Example 1 The preparation method of the platinum-nickel catalyst of Comparative Example 1 included the following steps: 0.416 g of platinum acetylacetonate and 0.54 g of nickel acetate were placed in a three-necked flask of an organic system composed of 1.6 mL of oleylamine, 1.6 mL of oleic acid, 9.6 mL of o-dichlorobenzene and 64 mL of diphenyl ether; it was heated to 200 °C at a heating rate of 15 °C / min, held for 30 min and then cooled to room temperature. The prepared platinum-nickel nanoparticles were separated, and after being repeatedly centrifugally washed with a mixed solution of ethanol and n-hexane at a centrifugal speed of 10,000 rpm, every 0.2 g of platinum-nickel nanoparticles was dispersed in 45 mL of chloroform to obtain a platinum-nickel nanoparticle suspension.

[0091] 0.416 g of KB600 was dispersed in 50 mL of chloroform to obtain the carbon material suspension of Comparative Example 1. The carbon material suspension and the platinum-nickel nanoparticle suspension were mixed and then deposited to obtain a precursor. The precursor was separated and washed with n-hexane, placed in a tubular furnace, heated to 400 °C in an argon atmosphere and held for 1 hour, cooled, and then immersed in a perchloric acid solution at 60 °C (concentration: 0.1 mol / L) for 12 hours for pickling treatment. Then it was thoroughly washed with ultrapure water until the pH value of the washing solution tended to be neutral, and dried to obtain the platinum-nickel catalyst of Comparative Example 1.

[0092] Comparative Example 2 The commercially available JM40 platinum-carbon catalyst with a platinum loading of 40% was used as Comparative Example 2.

[0093] The XRD characterizations of the catalysts of Example 1 and Comparative Example 1 were as Figure 3(PtNi / GC is Example 1, PtNi / KB is Comparative Example 1) As shown. It can be found that the XRD spectrum has three peaks at 41.4°, 48.5°, and 71.0°, corresponding to the middle of the standard diffraction peaks of platinum and nickel, respectively. There are no diffraction peaks corresponding to the standard peaks of pure Pt or pure Ni in the figure, which shows that the product mainly exists in the form of PtNi alloy. The diffraction peak of graphite (002) still appears near 2θ25.79°, indicating that the graphite structure in the carrier can remain stable during the reaction. The obvious diffraction peaks indicate that the obtained nanoparticles have good crystallinity.

[0094] The platinum-nickel metal loadings in the platinum-nickel catalysts prepared in Example 1 and Example 2 are shown in Table 1: Table 1 Pt wt. / % (from ICP) Ni wt. / % (from ICP) Example 1 23.51% 4.91% Example 2 30.33% 8.4% The TEM image of the platinum nickel catalyst prepared in Example 1 is as follows: Figure 4 and Figure 5 As shown, the particle size distribution histogram of the loaded platinum nickel nanoparticles is as follows Figure 6 As shown. g It can effectively describe the degree of dispersion. After calculation, the geometric standard deviation σ of the particle size distribution of the platinum nickel nanoparticles in Example 1 is g = e σln ≈ e*0.10555 ≈ 1.1113, σ g <1.12 indicates that the particle size distribution of the platinum-nickel nanoparticles in Example 1 is relatively concentrated and belongs to a narrow distribution. Combined with the XRD and high-resolution TEM analysis results of graphitized carbon (GC), the surface of the carbon carrier becomes smoother after graphitization treatment, which may have an adverse effect on the dispersion and loading of metal particles. Combined with the XRD and high-resolution TEM analysis results of Example 1 of the present application, the embodiment of the present application adopts the sol-gel method and solvent for dispersion and loading, and successfully loads an appropriate amount of platinum-nickel catalyst on the graphitized carbon material with a relatively serious loss of specific surface area. Moreover, the particle size of the platinum-nickel nanoparticles in the catalyst is small and uniform in size, and the particle size is precisely controlled at 2.5-4.5nm. The average particle size range is 3.4±0.3nm, and the activity is higher. After being evenly distributed on the graphitized carbon, the catalytic performance can be guaranteed.

[0095] The TEM image of the catalyst prepared in Comparative Example 1 is as follows: Figure 7 and Figure 8 As shown, the particle size distribution of the loaded platinum nickel nanoparticles is as follows Figure 9 As shown. After calculation, the geometric standard deviation σ of the particle size distribution of comparative example 1 g ≈ 1.11, the same σ g<1.12, indicating that the dispersion of its platinum-nickel nanoparticles is good and also belongs to a narrow distribution. It can be found that the carbon deposition on chloroform in Example 1 and Comparative Example 1 is relatively uniform, and the effect is better than that of the catalysts synthesized by the general impregnation method. The particle sizes are uniform. The size of the platinum-nickel nanoparticles supported on the non-graphitized KB600 in Comparative Example 1 is slightly higher than that in Example 1, and the average particle size ranges from 3.8 ± 0.4 nm. The TEM image of the catalyst prepared in Example 2 is as Figures 10 - 13 shown. From the distribution of platinum-nickel nanoparticles, agglomeration begins to occur in the platinum-nickel catalyst of Example 2 when the loading is increased.

[0096] The initial activity test results of Example 2 with a platinum loading of approximately 30% ( Figure 14 and Figure 15 where E-30 represents Example 2) are as Figure 14 (the measured polarization curve)- Figure 15 (the measured background current) and shown in Table 2: Table 2 MA at 0.9V vs. RHE (mA / mg) ECSA(Hupd) (m2 / g) Example 2 1704.02 55.84 It can be found that the initial activity of Example 2 decreases after the loading is increased. It can be seen that the higher the loading is not necessarily the higher the activity, and it will instead affect the catalytic performance after agglomeration occurs.

[0097] The cyclic activity test was carried out on the platinum-nickel catalysts prepared in Example 1 and Comparative Example 1: (1) Respectively take 5.0 mg of the platinum-nickel catalyst powder prepared in Example 1 or Comparative Example 1, add 4.9 mL of formic acid and 0.1 mL of ultrapure water, then add 25 μL of 0.5 wt% Nafion solution, and ultrasonically disperse for 40 min. After uniform dispersion, a slurry is obtained. Use a pipette to take 10 μL of the slurry and drop it on a rotating disk electrode, and use the rotary drying method to obtain a working electrode with a uniform catalyst film layer on the surface for electrochemical testing.

[0098] (2) Use a rotating disk electrode test system and an electrochemical workstation produced by PINE Company of the United States to evaluate the electrochemical performance of the catalyst. The test process is carried out in a standard three-electrode system. The rotating disk electrode with a catalyst film layer is used as the working electrode, the reversible hydrogen electrode is used as the reference electrode, and a Pt wire is used as the counter electrode. The test electrolyte is 0.1 M HClO4 solution.

[0099] (3) Before the electrochemical test, high-purity argon gas is introduced into 80 mL of 0.1 M HClO4 solution until the electrolyte is saturated with argon gas, and the three-electrode system is scanned at a scanning rate of 200 mV s -1 , and the scanning range is 0.05~0.8 V (vsRHE) to activate the formed working electrode.

[0100] After the activation is completed, the test is carried out by cyclic voltammetry (CV) at a scan rate of 20 mV s in an argon-saturated 0.1 M HClO4 solution between 0.05 and 1 V. Among them, the in-situ cyclic voltammetry curve is obtained at a potential of 0.05 V vs RHE, and the ECSA is calculated. -1 The linear sweep voltammetry (LSV) test is completed in an O2-saturated 0.1 M HClO4 solution between 0.05 and 1 V, and the scan rate is 20 mV s. The polarization curve of ORR is measured by linear sweep voltammetry, showing the results obtained by the electrocatalyst. Then, the mass activity (MA) is calculated according to the polarization curve and the amount of Pt on the electrode. -1 V vs RHE, and the ECSA is calculated.

[0101] The stability of the catalyst is tested by performing 10,000 ADT cycles at a scan rate of 100 mV s between 0.34 and 0.69 V (vs RHE), and a total of 5 cycles of 10,000 times are carried out. After each cycle, steps (2)-(4) are repeated to test the performance change. -1 The electrochemically active surface area (ECSA) of the catalyst is calculated by measuring the hydrogen atom adsorption and desorption region (Hupd) in the CV curve.

[0102] (5) The stability of the catalyst is tested by performing 10,000 ADT cycles at a scan rate of 100 mV s between 0.34 and 0.69 V (vs RHE), and a total of 5 cycles of 10,000 times are carried out. After each cycle, steps (2)-(4) are repeated to test the performance change. -1 The electrochemically active surface area (ECSA) of the catalyst is calculated by measuring the hydrogen atom adsorption and desorption region (Hupd) in the CV curve.

[0103] The test results of Example 1 are as (the background current measured separately for the Pt-Ni catalyst of Example 1 under 5 cycles of 10,000 times), (the polarization curve measured separately for the Pt-Ni catalyst of Example 1 under 5 cycles of 10,000 times), (the ECSA measured separately for the Pt-Ni catalyst of Example 1 under 5 cycles of 10,000 times), (the MA measured separately for the Pt-Ni catalyst of Example 1 under 5 cycles of 10,000 times) and shown in Table 3:

[0104] The test results of Example 1 are as Figures 16 - 19 ( Figure 16 The background current measured separately for the Pt-Ni catalyst of Example 1 under 5 cycles of 10,000 times, Figure 17 The polarization curve measured separately for the Pt-Ni catalyst of Example 1 under 5 cycles of 10,000 times, Figure 18 The ECSA measured separately for the Pt-Ni catalyst of Example 1 under 5 cycles of 10,000 times, Figure 19 The MA measured separately for the Pt-Ni catalyst of Example 1 under 5 cycles of 10,000 times) and shown in Table 3: Table 3 MA at 0.9V vs. RHE (mA / mg) Before and after comparison ECSA(Hupd) (m2 / g) Before and after comparison Initial activity 2947.22 60.39 Ten thousand cycles 3505.66 18.95%↑ 59.78 1.01%↓ Twenty thousand cycles 4265.19 44.72%↑ 63.58 5.28%↑ Thirty thousand cycles 3123.65 5.99%↑ 59.88 0.84%↓ Forty thousand cycles 3568.61 21.08%↑ 63.33 4.87%↑ Fifty thousand cycles 2658.33 9.80%↓ 58.43 3.25%↓ The test results of Comparative Example 1 are as Figure 20 (The background current measured separately for the Pt-Ni catalyst of Comparative Example 1 under 5 cycles of 10,000 times)- Figure 21 (The polarization curve measured separately for the Pt-Ni catalyst of Comparative Example 1 under 5 cycles of 10,000 times) and shown in Table 4: Table 4 MA at 0.9V vs. RHE (mA / mg) Before and after comparison ECSA(Hupd) (m2 / g) Before and after comparison Initial activity 3412.64 47.78 Ten thousand cycles 3658.26 7.20%↑ 52.61 10.11%↑ Twenty thousand cycles 3476.79 1.88%↑ 57.77 20.90 %↑ Thirty thousand cycles 3323.64 2.61%↑ 63.10 32.06%↑ Forty thousand cycles 2927.55 14.39%↓ 68.81 44.01%↑ Fifty thousand cycles 2251.68 34.02%↓ 71.23 49.08%↑ The activity comparison diagrams of Example 1, Comparative Example 1 and Comparative Example 2 are as shown in Figure 22 ( Figure 22 In it, a is the comparison of the initial measured background currents of Example 1 (PtNi / GC), Comparative Example 1 (PtNi / KB) and Comparative Example 2 (JM40), b is the comparison of the initial measured polarization curves of Example 1, Comparative Example 1 and Comparative Example 2, c is the bar comparison of the mass activity and specific activity of Example 1, Comparative Example 1 and Comparative Example 2, d is the comparison of the background currents measured before and after 50,000 cycles of testing for Example 1 and Comparative Example 1, e is the comparison of the polarization curves measured before and after 50,000 cycles of testing for Example 1 and Comparative Example 1, f is the bar comparison of the activities measured separately for Example 1 and Comparative Example 1 under 5 cycles of 10,000 times). It can be found from the comparison of the test results that the stability of Comparative Example 1 is relatively low, and the activity drops rapidly after the cyclic test. And during the test, the potential cycling causes the reconstruction of the catalyst surface, and the Ni atoms on the surface of the platinum-nickel alloy nanoparticles may be partially dissolved, exposing more Pt active sites, resulting in an increase in the electrochemically active (ECSA) area. While the stability of the high-performance platinum-based catalyst supported on graphitized carbon prepared in Example 1 is significantly improved, and it can still maintain a high catalytic activity after multiple cyclic tests, the change in the electrochemically active area is small, and the stability is high.

[0105] Then, MEA tests were carried out on the platinum-nickel catalysts prepared in Example 1 and Comparative Example 1. The steps include: (1) Preparation of membrane electrode.

[0106] Preparation of catalyst slurry: Disperse the platinum-nickel catalyst of Example 1 or Comparative Example 1 in a mixed solvent of ultrapure water, isopropanol and 5wt% Nafion solution. Control the total ratio of Nafion to the graphitized carbon support to be 0.7 to ensure the uniform distribution of the ionomer and the catalyst.

[0107] Slurry dispersion: Place the mixed slurry in an ice-water bath and use an ultrasonic cleaner for ultrasonic treatment until the slurry is uniformly dispersed without particle precipitation.

[0108] Catalyst coating: Use the catalyst coated membrane (CCM) method to uniformly coat the slurry on the proton exchange membrane to form a catalytic layer. The electrode active area is 25 cm².

[0109] (2) Single cell assembly.

[0110] Installation of membrane electrode: Install the prepared membrane electrode (MEA) into the fuel cell test workstation.

[0111] Gas diffusion layer and bipolar plate configuration: A gas diffusion layer (GDL) and a bipolar plate are installed on both sides of the membrane electrode to ensure good gas transport and current collection. Among them, the operating conditions are as follows: the cell temperature is 75 °C, the relative humidity is 100%, the back pressure (relative to the atmosphere) is 150 kPa, and the H2 / air stoichiometric ratio (excess coefficient) is 1.5:2.0. N2 and H2 are supplied to the cathode and anode at 0.2 standard liters per minute (NLPM), respectively.

[0112] According to the recorded potential and current density data, a polarization curve is plotted to evaluate the power density of the cell. The test results of Example 1 are as Figure 23 shown in (polarization curve and power density - current density curve) and Table 5, and the test results of Comparative Example 1 are as Figure 24 shown in (polarization curve and power density - current density curve) and Table 5: Table 5 <![CDATA[V (0.8 A·cm -2 )]]> <![CDATA[Peak power density W·cm -2 > Comparative Example 1 0.705 1.025 Example 1 0.710 1.032 It can be found that the high-performance platinum-based catalyst supported on graphitized carbon provided in Example 1 of this application can also achieve a relatively high peak power density at a relatively low platinum loading (about 23%), and has good catalytic activity.

[0113] In this application, the ultra-high temperature graphitization treatment has a significant impact on the graphitization degree, specific surface area and pore structure of the carbon material. These changes directly affect the performance of the catalyst. For example, the reduction of the specific surface area will affect the loading amount of the catalyst and limit the activity. In this application, by optimizing and adjusting the preparation and loading distribution of the platinum-based catalyst, the required loading amount is ensured and the dispersion of the metal particle catalyst is improved, so that the activity of the catalyst is enhanced. At the same time, the stability is also improved by the loading of graphitized carbon, providing a feasible strategy for the preparation and good application of the catalyst. The mass activity of the prepared catalyst is evaluated and verified through electrochemical tests, which proves that it improves the corrosion resistance of a single cell under the actual start / stop conditions of fuel cell vehicles, providing an innovative solution for breaking through the life bottleneck of fuel cell commercial applications.

[0114] It should be understood that the application of this application is not limited to the above examples. For those of ordinary skill in the art, improvements or transformations can be made according to the above description, and all these improvements and transformations should fall within the protection scope of this application.

Claims

1. A high-performance platinum-based catalyst supported on graphitized carbon, comprising graphitized carbon and platinum-based nanoparticles with uniform size, characterized in that, The platinum-based nanoparticles are uniformly dispersed and anchored on the surface of the graphitized carbon; The average particle size of the platinum-based nanoparticles is 3-4 nm, and the particle size distribution range is within ±0.5 nm; The degree of order R of the graphitized carbon satisfies R = I D / I G = 0.9 - 1.1; I D is the peak value of the D peak in the Raman spectrum of the graphitized carbon, I G is the peak value of the G peak in the Raman spectrum of the graphitized carbon; The platinum loading of the high-performance platinum-based catalyst supported on the graphitized carbon is 20-25%; The geometric standard deviation σ of the particle size distribution of the platinum-based nanoparticles g < 1.12 2. The graphitized carbon-supported high-performance platinum-based catalyst according to claim 1, wherein The average particle size of the platinum-based nanoparticles is 3.4-3.9 nm, and the particle size distribution range is within ±0.3 nm.

3. A preparation method of a graphitized carbon-supported high-performance platinum-based catalyst, characterized in that, It includes the following steps: Mix the graphitized carbon suspension and the platinum-based nanoparticle suspension and then deposit them to obtain a precursor; Separate and wash the precursor, then dry it, heat it in an inert atmosphere and keep it warm, cool it, perform pickling, and then wash and dry it to obtain the high-performance platinum-based catalyst supported on the graphitized carbon.

4. The preparation method of the high-performance platinum-based catalyst supported on graphitized carbon according to claim 3, wherein, The graphitized carbon suspension is prepared by dispersing graphitized carbon in an organic solvent; The platinum-based nanoparticle suspension is prepared by dispersing platinum-based nanoparticles in an organic solvent; The organic solvent is chloroform.

5. The preparation method of the high-performance platinum-based catalyst supported on graphitized carbon according to claim 4, characterized in that, The preparation method of the platinum-based nanoparticles includes the following steps: Add a platinum precursor and a transition metal precursor to an organic system composed of oleylamine, oleic acid, o-dichlorobenzene, and diphenyl ether for reaction, separate the solid and then wash it; Every 0.2 g of the platinum-based nanoparticles is dispersed in 30-60 mL of the organic solvent.

6. The preparation method of the high-performance platinum-based catalyst supported on graphitized carbon according to claim 5, characterized in that, The process of the reaction is to heat to 150-270 °C at a rated heating rate, keep it warm for 10 min-120 min, and then cool it to room temperature; the rated heating rate is 15-20 °C / min; The platinum precursor is platinum acetylacetonate, and the transition metal precursor is one or more of nickel acetate, ruthenium acetylacetonate, cobalt acetylacetonate, and nickel acetylacetonate; The mass ratio of the platinum acetylacetonate to the transition metal precursor is 1:0.5-2.3, and for every 0.2-0.5 g of the platinum acetylacetonate, 1.6 mL of oleylamine, 1.6 mL of oleic acid, 9.6 mL of o-dichlorobenzene, and 64 mL of diphenyl ether are used; The washing is carried out by repeatedly centrifuging with a mixture of one or both of ethanol or n-hexane, and the centrifugation speed is 10000 rpm.

7. The preparation method of the high-performance platinum-based catalyst supported on graphitized carbon according to claim 6, wherein The graphitized carbon suspension and the platinum-based nanoparticle suspension are mixed in a ratio of 0.9-1.1:1 by the mass ratio of graphitized carbon to platinum acetylacetonate.

8. The preparation method of the high-performance platinum-based catalyst supported on graphitized carbon according to claim 4, characterized in that, Every 0.35 g of the graphitized carbon is dispersed in 30-50 mL of the organic solvent; The preparation method of the graphitized carbon includes the following steps: Place the amorphous carbon material in a vacuum high-pressure furnace, perform high-temperature treatment at 1800-2600 °C in argon for 75 min, and naturally cool it to room temperature; The amorphous carbon material is KB600.

9. The preparation method of the high-performance platinum-based catalyst supported on graphitized carbon according to claim 3, wherein, The temperature of the heating is 250-550 °C, and the holding time is 10 min-10 h.

10. The preparation method of the high-performance platinum-based catalyst supported on graphitized carbon according to claim 3, characterized in that, The conditions for pickling are to soak the precursor in an acidic solution at a temperature of 50-70 °C for 12 hours; Every 0.3-0.4 g of the precursor is soaked in 15 ml of the acidic solution; The concentration of the acidic solution is 0.1-0.15 mol / L; The acid in the acidic solution is one of perchloric acid, sulfuric acid, nitric acid, and acetic acid; The washing is carried out by repeatedly washing with n-hexane; The washing conditions are repeated washing with ultrapure water until the washing liquid tends to be neutral; The inert atmosphere is argon.

Citation Information

Patent Citations

  • Method for preparing electrode catalyst of Nano particles of metal platinum under load of Nano carbon cage with thin wall

    CN101049559A

  • Method for improving dispersion of nano metal grains on surface of graphitized carbon carrier

    CN101816956A

  • Fuel cell catalyst graphitized carbon carrier, preparation method thereof and fuel cell catalyst employing graphitized carbon carrier

    CN108649243A

  • Preparation method of efficient stable Pt / GC catalyst

    CN108682874A

  • Fuel cell catalyst, preparation method thereof and fuel cell

    CN114188559A

Cited By

  • Oxygen-enriched microporous carbon-loaded platinum catalyst as well as preparation method and application thereof

    CN121035239A